RETRACTED: Intensitas Konsumsi Pangan Lokal Sumber Karbohidrat Non Beras dalam Upaya Diversifikasi Pangan di Desa Hargorejo Kecamatan Kokap Kabupaten Kulon Progo - Deden Mutakin (Jurnal Pendidikan Geografi: Kajian, Teori, dan Praktek dalam Bidang Pendidikan dan Ilmu Geografi, 2018)
Following a rigorous, carefully concerns and considered review of the article published in Jurnal Pendidikan Geografi to article entitle “Intensitas Konsumsi Pangan Lokal Sumber Karbohidrat Non Beras dalam Upaya Diversifikasi Pangan di Desa Hargorejo Kecamatan Kokap Kabupaten Kulon Progo” Vol 23, No 1 (2018), DOI: http://dx.doi.org/10.17977/um017v23i12018p009.This paper has been found to be in violation of the Jurnal Pendidikan Geografi publication principles and has been retracted.The article contained redundant material, the editor investigated and found that the paper published in Jurnal Geografi GEA, Vol. 17, No. 1 (2017), DOI: http://dx.doi.org/10.17509/gea.v17i1.5943.The document and its content has been removed from Jurnal Pendidikan Geografi, and reasonable effort should be made to remove all references to this article.